Cultural scorecards: a call for participatory Means of monitoring and assessment - Singhal , Arvind; Durá, Lucía (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
Social change professionals increasingly recognize that expert-derived traditional indicators of change in participant knowledge, attitudes, and practices (KAP) are inadequate to estimate program effectiveness. This article explores the potential of participatory research methods as a means for generating new indicators of change. The proposed indicators, cultural scorecards, are locally-relevant, culturally-embedded, metrics for assessing what constitutes “change” for the end-user. Examples of cultural scorecards from three participatory assessment projects in Uganda, India, and Perú are analyzed to illustrate the value they add to current traditions of monitoring, assessment, and impact evaluation. This analysis raises two main implications (1) one related to the epistemological value of cultural scorecards, and (2) one that speaks to the potential of employing cultural scorecards in all types of interventional research.